القضاء بالمغرب الأوسط في العهد الرستمي (160-296 هـ /777-909 م ) - فرج زليخة; اشراف: محمد حصباية (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
العنوان :القضاء بالمغرب الأوسط في العهد الرستمي (160-296ه/777-909م) يعتبر القضاء من أشرف الوظائف وأهمها عند الدول الإسلامية بصفة عامة والدولة الرستمية بصفة خاصة ،حيث كانت نشأة القضاء الرستمي مع مؤسس الدولة عبد الرحمان بن رستم سنة 160ه/777م في تيهرت، كما حضي باهتمام كبير من قبل الأئمة بعده ، أعلت الدولة الرستمية من شأن القضاة مما أكسبهم هيبة لدى هامة الناس وخاصتهم، كما تمتع القضاة بالاستقلالية وعدم تدخل الأئمة في شأنهم القضائي، فأصبح القضاء أكثر تنظيما من خلال مجلسه و استعانته بمختلف النظم القضائية التي أسهمت في استقرار الدولة،من خطط مكملة لعمله كالحسبة والشرطة والمظالم ،كما نجد أن القاضي بالمغرب الأوسط كان نزيها صارما في تطبيق أحكام الشريعة التي استنبطها من القرآن والسنة، وقد وثقت لنا المصادر التاريخية بنوعيها :الإباضية والمالكية تلك الصرامة والنزاهة في تنفيذ الحدود على من صدرت ضده جنحة من مختلف طبقات المجتمع بلا تمييز أو تحيز أو جور . Study Summary: Title: Judiciary in Central Morocco during the Rustamid Era (160-296 AH / 777-909 AD) The judiciary is considered one of the most honorable and important functions in Islamic states in general, and in the Rustamid state in particular. The Rustamid judiciary was established with the founder of the state, Abd al-Rahman ibnRustam, in 160 AH / 777 AD in Tihert, and it received significant attention from the imams who succeeded him. The Rustamid state elevated the status of judges, granting them prestige among both the elite and the general populace. Judges enjoyed independence, with no interference from the imams in judicial matters, which led to a more organized judicial system through its council and the implementation of various judicial frameworks that contributed to state stability. This included complementary functions such as market oversight (hisba), policing, and grievance management. In Central Morocco, judges were known for their integrity and strictness in applying the laws derived from the Quran and the Sunnah. Historical sources, both Ibadi and Maliki, document the rigorousness and impartiality of judges in enforcing punishments on offenders from all social classes without discrimination, favoritism, or oppression.